On Art, Compassion, and Memory (2013)
ABSTRACT: The late twentieth century saw an upsurge of visual artworks that vindicate the importance of artworks that show the pain endured by victims of political violence in the name of art’s unique ability to create shared memories. However, it is unclear what kind of memories art can create, and how can it create them. One common answer is that art can communicate empathically the most intimate perceptual aspects of pain and engrave them deeply in the spectator’s mind. This paper proposes to consider that question and evaluate this answer within the framework provided by the cognitive theory of emotions (Nussbaum 2003; Goldie 2000). I will first provide an analysis of an artwork by Colombian artist Doris Salcedo with the help of the theory of “criterial prefocusing” (Carroll 1998). This allows me to claim that the artistic and political importance of this artworks derives from the fact that it does not only try to generate empathy, but models it through compassion. The strength and depth of the emotion makes the experience memorable, but the cognitive structure of compassion imposes certain conditions in what kind of memory can be generated: it’s a memory not of the events recreated and not from the point of view of the victim, but a memory of the experience of the work and from the point of view of the spectator.